Development of digital signage for primary school using raspberry pi - Gunawan, Teddy Surya; Ginting, Arjuna; Md Sharif, Ahmad Syukri; Harahap, Nur Anzelina; Sophian, Ali; Ginting, Ramadhanu (Turkbilmat Egitim Hizmetleri, 2021)
Nowadays, digital signage is a modern advertisement alternative that took over billboards and other traditional advertisements. In the context of education, digital signage provides students, teachers, and parents with an effective way of communication. This research proposed designing and developing low-cost digital signage using Raspberry Pi to be stationed at primary school. An LCD monitor and Raspberry Pi 4 single-board computer were utilized to display various informative content, such as examination date, daily schedule, and other announcements. Two methods were proposed, including Screenly and WordPress on a web server. The WordPress version needs to install PHP, MySQL, and Nginx web server, which can be accessed and updated remotely. Results showed that the free version of Screenly would be adequate for a simple announcement, but the developed WordPress version will be more appropriate and flexible for the primary school purpose.